ANALISIS HUBUNGAN SISTEM INFORMASI MANAJEMEN DENGAN EFEKTIVITAS KERJA PEGAWAI NEGERI SIPIL PADA BAGIAN PENGOLAHAN DATA ELEKTRONIK PROVINSI SULAWESI TENGGARA - Sahrun Mane (Journal Publicuho, 2019)
This study aims to determine the implementation of management information systems and the effectiveness of Civil Servants working in the Electronic Data Processing Section of Southeast Sulawesi Province, and to find out the relationship between Management Information Systems and the Effectiveness of Civil Servants Work in the Electronic Data Processing Section of Southeast Sulawesi Province.The population in this study were all employees with the status of Civil Servants working in the Electronic Data Processing Section of Southeast Sulawesi Province, totalling 32 people. Sampling is done by using the saturated sample method (census), which is to use the entire population as a sample (respondent) besides that it is used by 2 informants namely the Head of Section and Head of the Electronic Data Processing Subdivision.In this study used product-moment correlation analysis and qualitative analysis.The results of the study showed that the management information system used by the Electronic Data Processing Section of Southeast Sulawesi Province had on average been good, and the work effectiveness of civil servants in the Electronic Data Processing Section of Southeast Sulawesi Province was also good on average.